Bibliometric Insights into Global Efforts in Protecting Children's Rights - Rijal, Syamsu; Wamafma, Filep (Eastasouth Institute, 2024)
This bibliometric study provides an in-depth analysis of the research landscape in children's rights over the past three decades, utilizing a variety of visualization tools to map out author collaborations, thematic clusters, research trends, and potential areas for future exploration. Through the analysis of key publication databases, this paper identifies robust networks of collaboration among authors and highlights predominant thematic areas such as child protection, legal frameworks, and the impacts of global health policies on children. The temporal analysis reveals a noticeable shift in research focus, from traditional protection measures to more contemporary issues such as digital safety and global policy initiatives. Furthermore, areas with less research concentration, including the integration of sports in rights promotion and the implications of digital advancements on children, are identified as potential opportunities for future studies. This study underscores the dynamic nature of children's rights research and its evolution in response to both enduring and emerging challenges affecting children globally.